Knowledge and Awareness towards Oral Medicine Specialty among Medical Practitioners in Tripoli, Libya: A cross-sectional study - Reema Ben Saleh; Intesar Rih; Naima Elbreki (AlQalam Journal of Medical and Applied Sciences, 2025)
Oral medicine (OM) is a specialty of dentistry that is concerned with the nonsurgical management of disorders and conditions affecting the oral cavity and the oral health care of medically compromised patients. Medical practitioners play a crucial role in integrating oral health into general health care, as early recognition and management of these often-treatable conditions can lead to improved health outcomes. However, inadequate awareness of oral health and related disciplines appears to be common among medical practitioners. This study was conducted to assess the level of awareness and knowledge score of OM specialty among medical practitioners, the volume of OM clinical cases that they come across in their routine practice, and to whom they refer them. A cross-sectional, printed, and validated questionnaire-based study was conducted among 114 medical practitioners from various specialties working in public healthcare centers and private practice in Tripoli, Libya. This study was conducted between December 2024 and April 2025. The study revealed a notable lack of awareness regarding the OM specialty among the participating medical practitioners in Tripoli. A significant majority (73.7%, n = 84) reported having never heard of the specialty. In contrast, only 26.3% (n = 30) of the respondents. Frequent incidence of oral mucosal lesions (34.2%), followed by Oral manifestation of systemic diseases (28.9%), and rare incidence of salivary gland disorders (56.1%) and facial pain and Temporomandibular Joint (TMJ) disorders (47.4%) were noted in their routine practice. OM specialists received relatively few referrals across all conditions, with their highest rate noted in relation to oral mucosal lesions (just over one-fifth, 20.2%, n=23). The distribution of oral medicine knowledge scores among medical practitioners revealed a mean of 7.46 ± 1.75. Categorically, the majority of participants (67.5%) demonstrated moderate (fair) knowledge, 27.2% displayed good knowledge, and a minority (5.3%) were classified as having poor knowledge, and intra-group agreement on knowledge ratings was assessed using Kendall’s coefficient of concordance (W). The MSc group demonstrated the highest degree of agreement (W=0.369, P < 0.001). This study provides evidence on the profound interdisciplinary gap between medicine and dentistry. There is slight knowledge and very low awareness to word the OM specialty among medical practitioners in Tripoli, Libya, indicating that OM specialists should spend more effort to increase awareness of the specialty and need more education, training, which will improve the quality of health care and bridge the gap between medicine and dentistry.